Application of Multidisciplinary Diagnosis and Treatment (MDT) clinical teaching model in the clinical teaching of some undergraduates of breast diseases in surgery - Nan Wang; Lin Li; Luhong Han; Shan Jiang; Youyi Xiong; Fang Wang; Yuanting Gu; Xinxing Wang (BMC Medical Education)
Abstract Background Breast surgery, emerging as an independent discipline with a wealth of specialist cases and an extensive case resource library in medical history. Contemporary clinical teaching faces challenges with traditional methods unable to address students' theoretical strength and practical limitations. The COVID-19 pandemic further strained learning environments, limiting students' exposure to patient diagnosis and treatment. Conventional clinical teaching, organized by disciplines, often results in technical isolation and a narrow clinical perspective, impeding the development of well-rounded medical professionals. Multidisciplinary Comprehensive Diagnosis and Treatment (MDT) emerges as a patient-centric, collaborative approach involving various medical departments in clinical decision-making. Despite its success in clinical settings, the effectiveness of MDT in undergraduate medical education remains largely unexplored. Methods This study conducted at the Breast Department of the First Affiliated Hospital of Zhengzhou University, aimed to compare the learning outcomes of clinical interns under traditional and MDT teaching modes. In a randomized controlled trial with 140 participants, the MDT group received comprehensive training from diverse healthcare professionals, while the traditional group had standard teaching. Evaluation included pre-test and post-test assessments on knowledge acquisition, skill acquisition, and clinical decision-making. Longitudinal analysis and statistical tests, including t-tests and multiple regression, were employed. Results A total of 140 clinical medicine students participated, randomly assigned to MDT (n = 70) and Traditional Teaching Mode (n = 70) groups. Key baseline characteristics, such as age, gender, and completion rates, were comparable between groups. For each group’s pre- and post-test scores, MDT group means consistently surpassed Traditional Teaching Mode, with significant differences (p < 0.05).Correlation analysis showed that there were no significant variable correlations between individual performance characteristics and test scores. Post-training, significant score improvements were observed in both groups across all tests (p < 2.2e-16). Utilizing the Wilcoxon rank sum test, pre-test differences were not significant. However, post-test scores favored the MDT group significantly (p = 0.0016, 2.8e-09, 3.6e-07). For students pursuing a master's, no statistically significant differences in specialty choice were observed between groups, though a trend towards more MDT students choosing surgical specialties was noted. Conclusion This study pioneers the application of the MDT teaching method in breast cancer clinical education, comparing its efficacy against traditional teaching modes. Findings demonstrate that MDT-based breast cancer diagnosis and treatment education is more efficient and optimized, offering a transformative basis for clinical undergraduate education reform in China. The results advocate for the reconfiguration of multidisciplinary consultation clinical teaching and traditional methods, promising enhanced educational outcomes and heightened medical student knowledge.